Familial risk of pleural mesothelioma increased drastically in certain occupations: A nationwide prospective cohort study. (November 2018) - Kharazmi, Elham; Chen, Tianhui; Fallah, Mahdi; Sundquist, Kristina; Sundquist, Jan; Albin, Maria; Weiderpass, Elisabete; Hemminki, Kari
Abstract: Objective: We aimed to explore the effect of occupation on familial risk of pleural mesothelioma in a nationwide cohort study design. Method: The nationwide Swedish Family-Cancer Database includes all Swedes born after 1931 and their biological parents, totalling 16.1 million individuals with about 2.3 million cancer patients. Hazards ratios (HRs) were calculated adjusting for age, sex and region of residence. Results: Having asbestos-related occupation in the absence of family history of mesothelioma increased risk of mesothelioma more than threefold (adjusted HR = 3.2, 95% confidence interval [CI]: 3.0–3.5). In those who had a history of mesothelioma in their first-degree relatives and an asbestos-related occupation, risk of mesothelioma dramatically increased compared with individuals without such occupations and family history (without chronic obstructive pulmonary disease [COPD] HR = 24, 95% CI: 15–39; with COPD 45, 95% CI: 15–141). In those who had a family history of mesothelioma and no history of an asbestos-related occupation, risk of mesothelioma did not show significant increase compared with those who had no family history of mesothelioma and no asbestos-related occupation (HR = 1.6; 95% CI: 0.7–3.8). Conclusion: First-degree relatives of patients with pleural mesothelioma had a drastic risk of developing this malignancy in case of certain occupations, which shows a gene–environment interaction is probable in risk of mesothelioma. Highlights: Patients with familial pleural mesothelioma are more sensitive to asbestos exposure than non-familial cases. Relatives of patients with mesothelioma had a drastic risk of developing this malignancy in case of exposure to asbestos. A gene–environment interaction is probable in risk of mesothelioma.